A Robust and Easy Protein Purification Method Using SpyDock-Modified Resin - Xiaofeng Yang; Zhanglin Lin; Ya Xiang; Binrui Chen; Zisha Lao (Bio-Protocol)
Protein purification is a critical step in both life sciences and biomanufacturing. Traditional affinity chromatography (AC) methods, including His-tag-based purification, provide high-purity proteins but are limited by the high cost of resins and the need for additional tag-removal steps. In this protocol, we present a reusable SpyDock-modified epoxy resin coupled with a pH-inducible self-cleaving intein for direct purification of proteins with authentic N-termini. This method enables efficient protein purification from cell lysates, achieving high purity (>90%) and yields comparable to the His-tag approach, without requiring tag removal. The SpyDock-modified resin protocol is robust, easy to implement, and cost-effective, making it suitable for both research and large-scale industrial applications.